The traditional jewelry of Egypt - Fahmy, Azza; Salem, Nehad (Cairo ; New York : The American University in Cairo Press, 2015)
In this illustrated book, Azza Fahmy, a world-renowned designer of jewelry based on traditional motifs, lays before us an Aladdin's cave of jewelry made in all corners of Egypt over the last one hundred years, collected through her extensive travels throughout the country.
Peasant and shaʻbi jewelry -- Desert jewelry -- Nubian jewelry -- Jewelry for special purposes -- Egyptian hallmarks.
Includes bibliographical references (page 216) and index.
Keywords: Jewelry -- Egypt; Jewelry making -- Egypt; Ethnic jewelry -- Egypt